A Study of the Implementation of International Treaties on Child Marriage in Ghana - Awuye, V.E. (University Of Ghana, 2018)
In 1998, Ghana enacted the children’s Act 560 (1998) to harmonize its national laws to the principle of the United Nations Convention on the Rights of the Child (UNCRC). This Act was enacted to protect children. Twenty years on, children in Ghana are still exposed to harmful practices which have extreme consequences on their development. Child marriage is one of the harmful practices to which children in Ghana remain exposed. Currently, the national child marriage prevalence rate stands at 21% in Ghana. This study assessed the implementation of international treaties on child marriage in Ghana. It explored the strategies by government to end child marriage as per international treaties ratified. It further explored the implementation of the treaties thus far and the contributions of development partners in addressing the problem of child marriage. The study was conducted using qualitative research methodology. Semi-structured interviews were conducted with selected persons with child protection mandates at the district and national levels including development partners UNICEF and International Needs Ghana. Case studies of child marriages survivors were also constructed through interviews with five girls from Hini, Gomoa Osbonpanyin, Gomoa Akwamu, Amissakrom and Eshiem. The findings show that Ghana has adequate laws to end child marriage and other child protection violations. The government has also made some strides in efforts to deal with the practice yet there are gaps between legal intent and practice. The challenge remains with the effective implementation of these treaties Ghana has signed as there are financial and technical constraints as well as tensions between statutory law and customary practices. It is concluded from these findings that for Ghana to be able to end child marriage by 2030, an effective bottom-up approach should be adopted in policy implementation and adequate financial and technical resources must be invested in the work of institutions with child protection mandates. It is mainly recommended that Community Child Protection Committees (CCPCs) be established to intervene in various child protection violations as the country does not have enough resources to make interventions, especially at the community level to ensure children are safe.
MA.
Keywords: International Treaties; Child Marriage; Ghana